2014
DOI: 10.1007/s10068-014-0250-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in color parameters of corn kernels during roasting

Abstract: Changes in color parameters (L*, a*, b*, ∆E*, h o , and C* values) of corn during roasting were investigated and subsequently described using mathematical models. Corn kernels were roasted for 50 min at 160, 180, 200, 220, and 240 o C. The L*, b*, h o , and C* values tended to decrease more rapidly as the roasting temperature and time increased up to 220 o C and 50 min, whereas a* and ∆E* values tended to increase. Variation of L* and ∆E* values was found to be proportional to the roasting temperature and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 17 publications
6
24
1
1
Order By: Relevance
“…The a * and b * value were increased while the L * value decreased of roasted samples of maize with increase in combinations of time and temperature in a pilot scale roasting which ultimately increased the BI value. The similar findings were reported by Chung et al () for laboratory scale roasting of maize. Increase in BI of the flour is attributed to discoloration of yellow pigment and decrease the value of lightness of the kernels due to heating could be as a result of Maillard reaction (nonenzymatic browning) and it can be controlled by roasting process variables (Zzaman & Yang, ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The a * and b * value were increased while the L * value decreased of roasted samples of maize with increase in combinations of time and temperature in a pilot scale roasting which ultimately increased the BI value. The similar findings were reported by Chung et al () for laboratory scale roasting of maize. Increase in BI of the flour is attributed to discoloration of yellow pigment and decrease the value of lightness of the kernels due to heating could be as a result of Maillard reaction (nonenzymatic browning) and it can be controlled by roasting process variables (Zzaman & Yang, ).…”
Section: Resultssupporting
confidence: 91%
“…The roasting process is known to induce desirable, and occasionally undesirable, changes in physicochemical (color, texture, composition, and flavor), and sensory (taste and aroma) attributes of roasted grains and nuts (Youn & Chung, ; Zzaman & Yang, ). Chung, Kim, Moon, and Youn () studied the color characteristic for the roasting of corn where they found that the time and temperature significantly enhanced the color (browning) kinetics and could be controlled only through the roasting process parameters. In addition, Grossmann, Mandarino, and Yabu () reported the structural changes caused by the mechanical damage to the corn kernels due to boiling/roasting and enzymatic degradation in cooked maize flour which was severely influenced the rate of water and oil absorption capacity (OAC).…”
Section: Introductionmentioning
confidence: 99%
“…e +b * and −b * values represent yellowness and blueness, respectively. e parameter hue angle (h°) expresses the color tone and is defined as red-purple: 0°, yellow: 90°, bluish green: 180°, and blue: 270° [25]. Total color difference (ΔE), browning index (BI), saturation index (SI), h°and whiteness index (WI) were calculated using Equations (3)-(8) [26]:…”
Section: Color Measurementmentioning
confidence: 99%
“…Visual color is an important quality criterion for roasted foods and may be assessed in terms of quantitative parameters such as L * , a * , b * , color differences (ΔE * ), hue angle (h°), and saturation or chroma (SI) values. Color also is an important quality indicator in the case of roasted foods, and optimized color parameters may be used as quality control indicators during the roasting processes [25,26].…”
Section: Color Measurementmentioning
confidence: 99%
“…[1] Lactoned erivatives also occur in microorganisms and animals, [2] fulfilling an umber of different functions. The biological activities, such as cytostatic, [3][4][5][6][7][8] antibacterial, [9][10][11][12] antiviral [13][14][15][16][17] or antifungal [18][19][20] activities,h ave applications in medicine. Sensory properties make them useful in the production of cosmetics and in the food industry,w here they are responsible for the smell and taste of many products.…”
Section: Introductionmentioning
confidence: 99%